A mental number line in human newborns. Issue 6 (5th March 2019) - Di Giorgio, Elisa; Lunghi, Marco; Rugani, Rosa; Regolin, Lucia; Dalla Barba, Beatrice; Vallortigara, Giorgio; Simion, Francesca
Abstract: Humans represent numbers on a mental number line with smaller numbers on the left and larger numbers on the right side. A left‐to‐right oriented spatial–numerical association, (SNA), has been demonstrated in animals and infants. However, the possibility that SNA is learnt by early exposure to caregivers' directional biases is still open. We conducted two experiments: in Experiment 1, we tested whether SNA is present at birth and in Experiment 2, we studied whether it depends on the relative rather than the absolute magnitude of numerousness. Fifty‐five‐hour‐old newborns, once habituated to a number (12), spontaneously associated a smaller number (4) with the left and a larger number (36) with the right side (Experiment 1). SNA in neonates is not absolute but relative. The same number (12) was associated with the left side rather than the right side whenever the previously experienced number was larger (36) rather than smaller (4) (Experiment 2). Control on continuous physical variables showed that the effect is specific of discrete magnitudes. These results constitute strong evidence that in our species SNA originates from pre‐linguistic and biological precursors in the brain. Abstract : Neonates, after being habituated to a certain number of dots, associated a smaller number with the left and a larger number with the right side. This evidence demonstrates that neonates spontaneously associate numbers with space.